2018
DOI: 10.3390/ijerph15122915
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Vaccination among 1999–2017 Birth Cohorts in Zhejiang Province: The Determinants Associated with Infant Coverage

Abstract: This study aimed to investigate the coverage of hepatitis B vaccine (Hep B) and its completeness and timeliness for birth cohorts from 1999 to 2017 in Zhejiang province, East China. Demographic characteristics and vaccination records of Hep B of children born from January 1, 1999 to June 31, 2017 were extracted from the Zhejiang provincial immunization information system. The timeliness of the first dose of Hep B (Hep B1) was defined as the proportion of children who received the Hep B1 within 24 hours after b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…Therefore, among the heavy metals in the Xiangjiang River, Cd and As are the major sources of carcinogenic risk. Previous studies have also found carcinogenic risks from exposure to arsenic and cadmium in surface water 49 , 50 . It has been shown that As in drinking water can cause liver cancer, lung cancer, hypertension, neuropathy, etc., and Cd can damage lung and trigger DNA mutation 24 , 51 .…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, among the heavy metals in the Xiangjiang River, Cd and As are the major sources of carcinogenic risk. Previous studies have also found carcinogenic risks from exposure to arsenic and cadmium in surface water 49 , 50 . It has been shown that As in drinking water can cause liver cancer, lung cancer, hypertension, neuropathy, etc., and Cd can damage lung and trigger DNA mutation 24 , 51 .…”
Section: Resultsmentioning
confidence: 93%
“…8 Within each setting, overall baseline birth dose coverage came from reported estimates but was distributed among facility and community births at a ratio of 2:1, with the relative likelihood of vaccination doubled and delivery more prompt in facilities than with community births (appendix p 4). 28 Annual age-specific, all-cause mortality probabilities were taken from the UN Population Division, reflective of 2015-20. 36 Populationweighted GBD region averages can be seen in the appendix (pp 3-4).…”
Section: Demographic and Epidemiological Inputsmentioning
confidence: 99%
“…Hepatitis B vaccines are widely used and effective for the prevention of new HBV infections. However, the overall success rate of hepatitis B vaccination is about 90% (Bruce et al, 2016; Hu et al, 2018). The outcome of HBV infection can vary dramatically, depending on both host and viral factors.…”
Section: Introductionmentioning
confidence: 99%